Developmet of Project Based Learning-Based Student Worksheets to Improve Problem-Solving Skills in Mathematics Learning for Grade V Elementary Schools - Armansyah, Armansyah; Nurhanurawati, Nurhanurawati; Fatkhur Rohman; Yulianti, Dwi (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This research aims to develop a mathematics student worksheet based on Project Based Learning on the material of cubes and blocks. Worthy, practical, and effective to measure the problem-solving abilities of fifth-grade elementary school students. This research is a type of Research and Development research (R&D), development is carried out referring to the Borg & Gall theory. The population in the research these are the fifth grade students of State Elementary School 1 Rajabasa Raya Bandar Lampung, The research sample was determined using a simple random sampling technique. The data collection tool data were collected using test instruments and questionnaires. The results of the study indicate that the Project Based Learning-based mathematics student worksheet has gone through a validation process by experts. Based on the assessment results, this student worksheet was declared very valid in terms of material, media, and language aspects. The practicality test conducted on educators and students also showed that the student worksheet was included in the very practical category for use in learning activities. Furthermore, the results of the effectiveness test showed a significant increase in mathematical problem-solving abilities after using the student worksheet. Thus, it can be concluded that the Project Based Learning-based mathematics student worksheet developed is feasible to use, practical to implement, and effective in improving the mathematical problem-solving abilities of fifth-grade elementary school students.